2011
DOI: 10.1007/s00125-011-2380-5
|View full text |Cite
|
Sign up to set email alerts
|

Both resistance- and endurance-type exercise reduce the prevalence of hyperglycaemia in individuals with impaired glucose tolerance and in insulin-treated and non-insulin-treated type 2 diabetic patients

Abstract: Aims/hypothesisThe present study compares the impact of endurance- vs resistance-type exercise on subsequent 24 h blood glucose homeostasis in individuals with impaired glucose tolerance (IGT) and type 2 diabetes.MethodsFifteen individuals with IGT, 15 type 2 diabetic patients treated with exogenous insulin (INS), and 15 type 2 diabetic patients treated with oral glucose-lowering medication (OGLM) participated in a randomised crossover experiment. Participants were studied on three occasions for 3 days under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
101
2
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 33 publications
13
101
2
6
Order By: Relevance
“…[2][3][4][5] Indeed, among adults with and without existing risk factors, numerous studies have reported significantly improved insulin sensitivity and glucose tolerance with structured RE interventions. 6,7 There is also compelling evidence to support the efficacy of progressive RE for glycemic control among children and adolescents, 8 even in the absence of weight loss. 9,10 However, because RE is known to elicit a potent insulin-sensitizing affect for hours after a single bout of training, [11][12][13] there is some speculation about whether it is merely the repeated acute responses to habitual RE that drive benefits for metabolic health, rather than any adaptive-response per se.…”
mentioning
confidence: 99%
“…[2][3][4][5] Indeed, among adults with and without existing risk factors, numerous studies have reported significantly improved insulin sensitivity and glucose tolerance with structured RE interventions. 6,7 There is also compelling evidence to support the efficacy of progressive RE for glycemic control among children and adolescents, 8 even in the absence of weight loss. 9,10 However, because RE is known to elicit a potent insulin-sensitizing affect for hours after a single bout of training, [11][12][13] there is some speculation about whether it is merely the repeated acute responses to habitual RE that drive benefits for metabolic health, rather than any adaptive-response per se.…”
mentioning
confidence: 99%
“…While many studies indicate that acute exercise lowers postprandial glucose (Gillen et al, 2012;Heden et al, 2015;Larsen, Dela, Kjaer, & Galbo, 1997;Larsen, Dela, Madsbad, & Galbo, 1999;Poirier et al, 2000;van Dijk et al, 2012;Rynders et al, 2014), others show either mixed effects (Ho, Dhaliwal, Hills, & Pal, 2010;Manders, Van Dijk, & Van Loon, 2010;Oberlin et al, 2014) or no effect (Baynard, Franklin, Goulopoulou, Carhart Jr, & Kanaley, 2005;Gonzalez, Veasey, Rumbold, & Stevenson, 2013;Knudsen, Karstoft, Pedersen, van Hall, & Solomon, 2014;Morishima, Mori, Sasaki, & Goto, 2014;Rose, Howlett, King, & Hargreaves, 2001). The four studies that have investigated the effects of acute aerobic (Larsen et al, 1997;Larsen et al, 1999;Poirier et al, 2001) or resistance (Heden et al, 2015) postmeal exercise on glucose control have all indicated a decrease in glucose and insulin in the postprandial period.…”
Section: Postmeal Exercisementioning
confidence: 99%
“…For example, studies using continuous glucose monitors (CGM) to assess glucose kinetics over a 24-hour period have shown beneficial effects following both moderate (Manders et al, 2010;Oberlin et al, 2013;van Dijk et al, 2012) and high-intensity (Gillen et al, 2012;Manders et al, 2010) exercise before a meal. Of these, no study indicated an attenuation of blood glucose in the initial two-hour postprandial period.…”
Section: Premeal Exercisementioning
confidence: 99%
“…37 As the effect of physical activity on glycemic control and body composition is well documented, 34,38 exercise training could be used as a first line of treatment for type 2 diabetes, and numerous studies have also showed the efficacy of HIIT [39][40][41]43 with regards to the effective management of the condition. For instance, decreases in average 24h blood glucose concentrations (~1mmol/l), postprandial excursions for breakfast, lunch and dinner, the prevalence of hyperglycemia (~33%), and increases in GLUT4 activity as well as reduced body fat levels, have previously been reported by studies examining the use of either HIIT or MICT in patients with type 2 diabetes.…”
Section: Insulin Sensitivitymentioning
confidence: 99%
“…For instance, decreases in average 24h blood glucose concentrations (~1mmol/l), postprandial excursions for breakfast, lunch and dinner, the prevalence of hyperglycemia (~33%), and increases in GLUT4 activity as well as reduced body fat levels, have previously been reported by studies examining the use of either HIIT or MICT in patients with type 2 diabetes. [39][40][41][42][43] This enhanced GLUT4 activity and/or glycogen synthesis/utilisation may be in part due to the up regulation of the transcription factor E3 (TFE3), which in mice has been shown to increase glycogen storage is and associated with up regulation of genes related to proteins related to glucose metabolism (glycogen synthase, GLUT4, Hexokinase II), 44 The lack of 'action' of insulin in type 2 diabetics has been linked to defects in the ability of insulin to phosphorylate the insulin receptor IRS-1, a molecule responsible for downstream regulation of insulin action in skeletal muscle. 45 Indeed it has been shown that regular exercise leads to up regulation of IRS-1 in humans.…”
Section: Insulin Sensitivitymentioning
confidence: 99%